Mobilities of Return: Pacific Perspectives 2017
DOI: 10.22459/mr.12.2017.07
|View full text |Cite
|
Sign up to set email alerts
|

Adding insult to injury: Experiences of mobile HIV‑positive women who return home for treatment in Tanah Papua, Indonesia

Abstract: This chapter explores the personal experiences of mobile HIV-positive indigenous women from Tanah Papua, Indonesia who returned to their home communities in need of social support and treatment. Little is known about the experiences of HIV-positive women returnees in general, and the contours and effects of the moral expectations and boundaries within home communities in particular. This paper draws on close-grained analysis of in-depth interviews and fieldwork conducted between 2009 and 2013 to suggest Papuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…There is a growing divide between elite men who are able to control goods and people and those who may suffer the brunt of regulation, collusion, and stigmatization. Economic exclusion and militarization have intensified men's concerns over women's morality, mobility, and sexuality, even as gender practices and values have become, for some men, an arena in which to disprove the alleged "backward" and "violent" propensities attributed to them by Indonesians (Munro 2017). Perhaps, as in other Melanesian contexts (see, eg, Bainton and Macintyre 2013), Dani men are sometimes seeking specific forms of power by embracing masculinities that may celebrate alcohol consumption.…”
Section: Discussion: Alcohol and The Reconfiguration Of Indigenous Mamentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing divide between elite men who are able to control goods and people and those who may suffer the brunt of regulation, collusion, and stigmatization. Economic exclusion and militarization have intensified men's concerns over women's morality, mobility, and sexuality, even as gender practices and values have become, for some men, an arena in which to disprove the alleged "backward" and "violent" propensities attributed to them by Indonesians (Munro 2017). Perhaps, as in other Melanesian contexts (see, eg, Bainton and Macintyre 2013), Dani men are sometimes seeking specific forms of power by embracing masculinities that may celebrate alcohol consumption.…”
Section: Discussion: Alcohol and The Reconfiguration Of Indigenous Mamentioning
confidence: 99%
“…4 My initial fieldwork involved living for about fifteen months with groups of Dani and Lani university students in their dormitories in North Sulawesi, a nearby province, interspersed with visits to their home areas in Wamena. This field work revealed that alcohol was believed to be fueling the hiv epidemic that disproportionately affects Indigenous highlander youth (Munro 2015a;Butt, Munro, and Numbery 2017). Later, my research focused on hiv, pregnancy, and sexuality among Dani and Lani youth in Wamena, including how Indigenous-led groups were responding to the growing hiv epidemic both in the highlands and in Manokwari, another Papuan city.…”
Section: * * *mentioning
confidence: 97%
“…Demikian halnya dengan Indeks Kesehatan Reproduksi Remaja (IKRRI) di Papua juga termasuk dari tiga yang terendah di Indonesia. Terkait dengan isu seksualitas, sejumlah studi sebelumnya banyak menyoroti keterkaitan antara tingginya prevalensi HIV/AIDS dan terbatasnya akses pengetahuan yang komprehensif tentang kesehatan reproduksi (Butt 2015). Melalui problematisasi HIV/ AIDS, beberapa studi juga menemukan kecenderungan budaya seksual aktif yang membentuk lingkaran persoalan yang tidak berujung.…”
unclassified